2009
DOI: 10.1186/1752-1947-3-68
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease as a potential cause of idiopathic portal hypertension: a case report

Abstract: IntroductionIdiopathic portal hypertension is a disorder of unknown etiology, clinically characterized by portal hypertension, splenomegaly and anemia secondary to hypersplenism.Case presentationA 54-year-old man was admitted to our hospital for evaluation of malaise, weight loss, abdominal swelling and lower limb edema. His paraclinical tests revealed pancytopenia, large ascites, splenomegaly and esophageal varices consistent with portal hypertension. Duodenal biopsy and serologic findings were compatible wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…This patient did not have any abnormal liver function tests. Zamani et al (23) have reported a 54-yr-old man with portal hypertension and CD, where his symptoms improved on a gluten-free diet. In pediatric age group, there are no published articles mentioning this association to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This patient did not have any abnormal liver function tests. Zamani et al (23) have reported a 54-yr-old man with portal hypertension and CD, where his symptoms improved on a gluten-free diet. In pediatric age group, there are no published articles mentioning this association to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an Italian study frankly indicated that serum TTG IgA ELISA determination based on TTG from guinea pig liver as the target antigen has a low sensitivity and specifity in screening patients with chronic liver disease for CD (29). A few studies have shown that celiac disease may coexist with IPH (10,19). In a recently published British study showed that 16% of patients with IPH found to have concomitant CD (30).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few reports about links between IPH and serologic markers of celiac disease. Most of them show the obscure relation is evident between the two distinct diseases (10,19,20). Our aim was to investigate the presence of tissue tranglutaminase antibodies in patients with IPH.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, only one recent publication reported a case of pancytopenia, large volume ascites, and splenomegalycausing idiopathic portal hypertension which was related to CD and subsequently improved on GFD [80]. The incidence of hyposplenism in CD varies from 16 to 77% of adult patients with CD [81,82], and the incidence is much lower in the pediatric population [83].…”
Section: Splenic Dysfunctionmentioning
confidence: 97%